Anti-hypercholesterolemic property of Phaleria macrocarpa fruit aqueous extract in hypercholesterolemia-induced rats - Chong, S. C.; Dollah, Mohamad Aziz (Sarawak Biodiversity Centre, 2008)
Phaleria macocarpa is a herb that been used in traditional medicine and has been claimed that P. macocarpa could cure hypercholesterolemia, diabetes, cancer and others. The scientific information on the therapeutic effects of this herb however is rather limited. In this study, antihypercholesterolemic property of various concentration of Pm aqueous fruit extract and the extend of its effects compared with Simvastatin was determined. In the study, 36 female rats were divided into 6 groups equally. Five groups were fed with 3% pure cholesterol during pre treatment (2 weeks) and treatment periods (4 weeks). Supplementation of 1 ml of the P. macocarpa extract (0, 67, 134 and 183 mg/kg bw) and Simvastatin (0.33 mg/kg bw) was given during treatment period. Blood samples were collected before and after the supplementation periods via cardiac puncture to analyze the total cholesterol (TG), triglycerides (TRG), high density lipid (HDL) and low density lipid (LDL) levels. The results shows that the mean difference of the total cholesterol after and before supplementation of P. macocarpa for negative control, 0, 67, 134, 183 mg/kg bw and simvastatin was 0.05±0.49, 0.87±1.56, -0.95±1.74, -0.66±1.66, -0.59±0.48 and -0.48±0.61 mmol/L. The mean difference for Triglycerides was -0.73±0.67, 0.28±1.74, -3.14±1.68, -1.24±1.16, -1.22±0.94 and 0.16±0.18. The mean difference for the HDL was 0.28±0.35, 0.13±0.50, 0.41±0.44, 0.11±0.45, 0.06±0.19 and -0.42±1.35 while the mean difference of the LDL was 0.07±0.08, 0.35±0.53, 0.22±1.28, -0.15±1.15, -0.48±0.75 and -0.05±0.54. The study concludes that P. macocarpa significantly reduced triglycerides level (P<0.05) and showed a tendency to reduce other lipid profiles. The effect of P. macocarpa supplementation was dose-dependant and P. macocarpa at the concentration of 44 mg/kg bw showed the same cholesterol reducing effect as simvastatin. Thus, P. macocarpa has anti hypercholesterolemic effect on hypercholesterolemic-induced rats.